Application Of Resource Based Learning (RBL) Model To Improve Natural Sciences Learning Outcomes On The Theme Of My Dream To Fourth Grade Students Of SD Negeri 2 Mekarsari In Academic Year Of 2019/2020 - Erika Safira Almas Khaerani; Suhartono Suhartono; Rokhmaniyah Rokhmaniyah (Universitas Sebelas Maret, 2020)
The aims of the study were: (1) to describe the application of Resource Based Learning (RBL) model, (2) to improve natural sciences learning outcomes to the theme of my dreams, and (3) to describe the obstacles and solutions to the application of Resource Based Learning (RBL) model. The research is Collaborative Classroom Action Research (CAR). It was conducted in three cycles. Each cycle consisted of planning, implementing, observing, and reflecting. The types of data were quantitative data and qualitative data. Data collection techniques used observation, interviews and tests. The results of the study indicated that: (1) the steps of RBL model to improve natural sciences learning outcomes to the theme of my dreams involved: a) identifying learning topics, b) arranging how to find information, c) gathering information, d) applying information, e) synthesizing information, and f) doing evaluation; (2) the application of Resource Based Learning (RBL) model improved natural sciences learning outcomes to the theme of my dreams, (3) the constraints were the students had difficulty in asking questions and expressing their opinions while the solution was the teacher motivated the students to dare in asking questions and expressing opinions.